2010
DOI: 10.1136/adc.2010.186338.157
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between type 1 diabetes and epilepsy in childhood?

Abstract: BackgroundThe relationship between type 1 diabetes and epilepsy in the paediatric population is unclear. There is evidence to suggest that antibodies to glutamic acid decarboxylase, an auto-antigen implicated in type 1 diabetes, are also associated with the development of epilepsy. However, seizures occurring in children with diabetes may be attributed to hypoglycaemia rather than an underlying seizure disorder.ObjectivesTo identify the number of children with both type 1 diabetes and epilepsy in the region, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is a risk factor for stroke, which itself is a risk factor for epilepsy, but a direct association between high blood pressure and epilepsy was not found in our study and not reported in any literature yet. But complying with the reports of other studies the association of diabetes was significant (p=0.01) There is evidence to suggest that antibodies to glutamic acid decarboxylase, an auto-antigen implicated in type 1 diabetes, are also associated with the development of epilepsy 44 .…”
Section: Resultmentioning
confidence: 51%
“…It is a risk factor for stroke, which itself is a risk factor for epilepsy, but a direct association between high blood pressure and epilepsy was not found in our study and not reported in any literature yet. But complying with the reports of other studies the association of diabetes was significant (p=0.01) There is evidence to suggest that antibodies to glutamic acid decarboxylase, an auto-antigen implicated in type 1 diabetes, are also associated with the development of epilepsy 44 .…”
Section: Resultmentioning
confidence: 51%